1996
DOI: 10.1074/jbc.271.13.7465
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Physical and Functional Interaction between Csk and Lck Which Involves the SH2 Domain of Csk and Is Mediated by Autophosphorylation of Lck on Tyrosine 394

Abstract: The COOH-terminal Src kinase (Csk) is responsible for the phosphorylation of the conserved, negative regulatory, carboxyl-terminal tyrosine of most of the Src family protein tyrosine kinases. Up to now, no stable binding of Csk to Src kinases has been detected. We therefore decided to analyze this interaction using two systems which allow detection of transient interaction. We produced and purified recombinant proteins in the glutathione S-transferase prokaryotic expression system. First, using real-time biosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…In contrast, Bougeret et al [46] recently reported that C-terminal phosphorylation of Lck by CSK is enhanced by interactions between autophosphorylated Tyr395 of Lck and the SH2 domain of CSK. Such an interaction, however, does not seem to occur between another autophosphorylated Src kinases, c-Fgr, and CSK [46]. Neither myristoylation nor the unique domain of Src kinase, moreover, seem to be necessary for phosphorylation by CSK [44].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, Bougeret et al [46] recently reported that C-terminal phosphorylation of Lck by CSK is enhanced by interactions between autophosphorylated Tyr395 of Lck and the SH2 domain of CSK. Such an interaction, however, does not seem to occur between another autophosphorylated Src kinases, c-Fgr, and CSK [46]. Neither myristoylation nor the unique domain of Src kinase, moreover, seem to be necessary for phosphorylation by CSK [44].…”
Section: Discussionmentioning
confidence: 86%
“…The same apparently applies to the SH2 and SH3 domains of CSK, considering that they are required for the in vivo regulation of Src kinases, but not for the in vitro phosphorylation of the C-terminal tyrosine residue [16,[43][44][45]. In contrast, Bougeret et al [46] recently reported that C-terminal phosphorylation of Lck by CSK is enhanced by interactions between autophosphorylated Tyr395 of Lck and the SH2 domain of CSK. Such an interaction, however, does not seem to occur between another autophosphorylated Src kinases, c-Fgr, and CSK [46].…”
Section: Discussionmentioning
confidence: 99%
“…Previous mutational and functional analyses suggest that several regions/residues on Lck could mediate either a direct Lck-Fyn interaction or interactions with intermediate molecule(s) as follows: the unique domain (55)(56)(57) and the SH2 (58) and SH3 (59) domains; the proline-mediated PPII conformation of the linker region (8); and the kinase domain (60,61) or specific residues within the C terminus (17,62). Toward determining which of these sequences might be involved in supporting Y505F Lck-Fyn complex formation, mutants with disabled function of each of these individual domains, and the last five amino acid truncated at the C terminus, were prepared on Y505F Lck cDNA template by site-directed mutagenesis.…”
Section: Panel) Lck-fyn Complex Formation Is Confined To Lipid Raftsmentioning
confidence: 99%
“…CSK appears to translocate to subcellular sites where its activity is probably required for normal regulation of Src-family kinases (Howell and Cooper, 1994). A number of CSK binding proteins have been identi®ed that may play an important role in membrane localization of CSK, and include GTPase-activating protein (GAP)-associated p62 (p62dok) (Neet and Hunter, 1995;Yamanashi and Baltimore, 1997;Carpino et al, 1997) and the Src-family member Lck (Bougeret et al, 1996).…”
Section: Ptp1b and Other Ptps That Might Target C-srcmentioning
confidence: 99%